2021
DOI: 10.3390/ijms221910496
|View full text |Cite
|
Sign up to set email alerts
|

Disulfiram Sensitizes a Therapeutic-Resistant Glioblastoma to the TGF-β Receptor Inhibitor

Abstract: Despite neurosurgery following radiation and chemotherapy, residual glioblastoma (GBM) cells develop therapeutic resistance (TR) leading to recurrence. The GBM heterogeneity confers TR. Therefore, an effective strategy must target cancer stem cells (CSCs) and other malignant cancer cells. TGF-β and mesenchymal transition are the indicators for poor prognoses. The activity of aldehyde dehydrogenases (ALDHs) is a functional CSC marker. However, the interplay between TGF-β and ALDHs remains unclear. We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…The evident importance of the tumor microenvironment in TGF-ß signaling calls for more advanced cancer models, including cells of the tumor stroma, in future studies [38]. Notably, similar studies investigating the effect of Galunisertib both in vitro and in vivo, found consistent antineoplastic effects [33,39,40]. It can therefore reasonably be assumed that the observed effect of Galunisertib on HNSCC cell lines might also be relevant in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…The evident importance of the tumor microenvironment in TGF-ß signaling calls for more advanced cancer models, including cells of the tumor stroma, in future studies [38]. Notably, similar studies investigating the effect of Galunisertib both in vitro and in vivo, found consistent antineoplastic effects [33,39,40]. It can therefore reasonably be assumed that the observed effect of Galunisertib on HNSCC cell lines might also be relevant in vivo.…”
Section: Discussionmentioning
confidence: 88%
“…The mechanism of action includes inhibition of HMG-CoA reductase by statins, resulting in downstream inhibition of Smad3 phosphorylation by Rho and ROCK [ 252 ]. Liu et al illustrated that the experimental compound galunisertib, which inhibits TGF-β receptor I kinase, can be deployed against GSCs in combination with the anti-alcohol drug disulfiram, which targets aldehyde dehydrogenases and sensitizes GSCs to the TGF-β receptor inhibitor [ 253 ]. Another inhibitor of the TGF-β receptor I, LY2109761, was shown to reduce expression of the CD44 stem cell marker in GSCs and reduce tumor growth and recurrence in an in vivo mouse model [ 254 ].…”
Section: Targeted Therapymentioning
confidence: 99%
“…C. Disulfiram in glioblastoma: With potential utility in treating glioblastoma with temozolomide, disulfiram irreversibly inactivates P-gp [171][172][173]. As with other cancers, the ALDH-positive glioblastoma subpopulation has other stem attributes, and is more chemotherapy resistant than the ALDH-negative subpopulation [158,[174][175][176]. D. Disulfiram in NSCLC: As it does in other cancers, ALDH contributes to driving stemness and, hence, cytotoxicity resistance, in NSCLC [177][178][179][180][181].…”
Section: Disulfirammentioning
confidence: 99%